The introduction of librarian tutors into the Teaching Evidence-Based Medicine week in Oxford, UK. - Nicola Pearce-Smith; Jo Hunter (2008)
Allocating a librarian tutor to each small group in an EBM workshop appears to benefit both health professionals and librarians. Participating in small group sessions at an EBM workshop provides a valuable opportunity for librarians to gain critical appraisal and teaching skills, which can be implemented on their return to the workplace.